Kesiapan Teknologi dan Penerimaan Pengguna Sistem Informasi Sumber Daya Terintegrasi (SISTER) Menggunakan TRAM - Ismiati, Maria Bellaniar; Andayani, Sri (Prahasta Publisher, 2022)
SISTER is an application that is used so that educators, namely lecturers, can manage and manage and integrate all educator data services. This makes it easier because SISTER is integrated with the DIKTI database so that the tridharma activities of higher education carried out by lecturers are well documented. Musi Charitas Catholic University (UKMC) which has urged all its lecturers to use SISTER since 2020. In using this new application (SISTER), it will definitely cause problems for some lecturers. These constraints such as several points in SISTER that are different from the BKD guide, when saving data will appear: something went wrong, if there is a revision by the assessor, the lecturer cannot see it and only the college admin can see it. The constraints above show how users are prepared and behave when facing new technology. This study will use the TRAM method to see Technology Readiness and User Acceptance of SISTER. The result is that all independent variables affect the dependent variable except for the discomfort and insecurity variables. And the respondents agree with all the existing hypotheses based on the evidence in the discussion section because they are in accordance with what they feel while using SISTER. For the level of readiness of information technology, SISTER is included on a scale of 9 because SISTER is no longer a prototype but has also become a complete system